Publisher Correction: Experimental Zika Virus Infection in the Pregnant Common Marmoset Induces Spontaneous Fetal Loss and Neurodevelopmental Abnormalities. Issue 1 (December 2018) - Seferovic, Maxim; Sánchez-San Martín, Claudia; Tardif, Suzette; Rutherford, Julienne; Castro, Eumenia; Li, Tony; Hodara, Vida; Parodi, Laura; Giavedoni, Luis; Layne-Colon, Donna; Tamhankar, Manasi; Yagi, Shigeo; et al.
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.